2012
DOI: 10.1155/2012/270425
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Development, Niches, and Signaling Pathways

Abstract: Hematopoietic stem cells (HSCs) play a key role in hematopoietic system that functions mainly in homeostasis and immune response. HSCs transplantation has been applied for the treatment of several diseases. However, HSCs persist in the small quantity within the body, mostly in the quiescent state. Understanding the basic knowledge of HSCs is useful for stem cell biology research and therapeutic medicine development. Thus, this paper emphasizes on HSC origin, source, development, the niche, and signaling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 172 publications
(199 reference statements)
4
77
0
8
Order By: Relevance
“…Many studies suggested that the bone marrow endosteum was the major HSC niche [6][7][8]. In this review, we will focus on the two hematopoietic niche and elucidate the cross-talk between niche and HSCs.…”
Section: The Hematopoietic Stem Cells Nichementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies suggested that the bone marrow endosteum was the major HSC niche [6][7][8]. In this review, we will focus on the two hematopoietic niche and elucidate the cross-talk between niche and HSCs.…”
Section: The Hematopoietic Stem Cells Nichementioning
confidence: 99%
“…A number of signaling pathways have been identified to be important for HSC behavior, including Hedgehog, Wnt, Notch, SDF-1 (CXCL12)/CXCR4 and Tie2/Ang-1signal-ing pathways [13]. This review will focus on the signaling pathways associated with HSCs.…”
Section: Signaling Pathwaymentioning
confidence: 99%
“…21 Studi pada mencit menunjukkan bahwa beta glucan spesifik dari jamur seperti Pleurotus ostreatus, Sclerotinia sclerotiorum dan Sparassis crispa, dapat meningkatkan hematopoiesis dan melindungi sel sumsum tulang, sehingga HSC dilepaskan ke darah perifer. 22,23 Hematopoietic stem cell (HSC)adalah sel induk dewasa yang memiliki potensi untuk memperbaharui diri dan berdiferensiasi menjadi sel darah yang berfungsi dalam beberapa aktivitas biologis: keseimbangan homeostasis, fungsi kekebalan tubuh, dan respon terhadap mikroorganisme dan inflamasi.Selain itu HSC diketahui dapat berdiferensiasi menjadi sel khusus (sifat plastisitas) seperti adipocytes, kardiomiosit, sel-sel endotel, fibroblas/myofibroblasts, sel-sel hati, osteochondrocytes, dan sel pankreas. 23 Sel beta pankreas mensekresi hormon insulin dalam jumlah yang cukup sesuai jumlah glukosa dalam darah.…”
Section: Pembahasanunclassified
“…Different models, vastly superimposable but however still not well known and characterized, have been reported to describe these processes [22] . The relative roles played by calcium fluxes and homeostasis and oxidative stream in the regulation of the HSC maintenance or differentiation are not well characterized in all these models.…”
Section: Research Highlightmentioning
confidence: 99%